THE EFFECT OF USING PROBLEM BASED LEARNING (PBL) METHOD TOWARD STUDENTS’ SPEAKING SKILL - Hamid, Sitti Maryam (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2014)
This research aimed at finding out whether or not the effect of using Problem Based Learning (PBL) method toward students’ speaking skill in term of vocabulary at the second year students of SMA Neg.1 Bantaeng. The researcher used quasi experimental research. The researcher took two classes, XI IPS 1 as a control class with 31 students, XI IPS 2 as an experimental class with 29 students. The researcher used cluster sampling technique. The research instrument was students retell interesting story or their experience to know the students’ vocabulary in speaking. The findings of this research shows that the value of t-test in the post-test is higher than t-table (2.875> 2.048). Problem Based Learning (PBL) Method improve the students’ vocabulary of experimental class in speaking English . The speaking achievement it was proved by the mean score of experimental class in pretest was 58.2 then improved to be 72.0, In control class the mean score of pre-test was 63.8, score of post-test 65.1. It means that there is improvement and effect by using problem based learning (PBL) method between experimental class and control class. Then in addition the t-test value is bigger than t-table value (2.875 >2.048). It means that there is significant difference between the students’ speaking achievement before and after using Problem Based Learning (PBL) method. From these findings, the researcher made conclusion that by using Problem Based Learning (PBL) Method can improve the students’ speaking English.